Gastropod chemoreception behaviors—Mechanisms underlying the perception and location of targets and implications for shellfish fishery development in aquatic environments - Yu, Zheng-Lin; Yang, Mei-Jie; Song, Hao; Zhang, Tao; Yuan, Xiu-Tang (Frontiers in Marine Science, 2023)
Chemoreception is one of the most important senses and it plays a key role in the survival and adaptation of animals to their environments. Many gastropods, such as Rapana venosa and Neptunea cumingii, have emerged as economically important shellfish. Meanwhile, invasive gastropods have destroyed commercial shellfisheries in many countries. Given the importance of chemoreception in the behavior of aquatic gastropods, the mechanism of their chemical perception has recently garnered attention. To provide a foundation for understanding the chemoreception of aquatic gastropods, we reviewed recent studies and summarized the chemoreception behaviors and mechanisms that gastropods use to perceive and locate targets in aquatic environments, along with relevant molecular and genetic insights. We highlight several of the implications of these studies for chemoreception-related research and shellfish fishery development. This review should aid in the rational development and utilization of gastropod resources as well as in controlling the populations of invasive species.